2013
DOI: 10.1097/mej.0b013e328359588f
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute atrial fibrillation in the emergency department

Abstract: The aim of the study was to provide an overview on the current evidence on the method of cardioversion in patients presenting with recent-onset atrial fibrillation at the emergency department. ISI Web of Science and MEDLINE were explored for articles published between January 2000 and December 2011 in English or Spanish for the keywords 'acute', 'recent-onset' or 'paroxysmal' AND 'atrial fibrillation' AND 'treatment' AND 'emergency'. Original published articles were included if they enrolled patients with atri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 0 publications
0
26
1
4
Order By: Relevance
“…Rate of complications was rather low, with single patients suffering serious complications including myocardial infarction, pulmonary embolism, or heart failure. A recent meta-analysis of AF cardioversion in emergency department shows comparable results [14].…”
Section: Discussionmentioning
confidence: 55%
“…Rate of complications was rather low, with single patients suffering serious complications including myocardial infarction, pulmonary embolism, or heart failure. A recent meta-analysis of AF cardioversion in emergency department shows comparable results [14].…”
Section: Discussionmentioning
confidence: 55%
“…As in other studies, this may reflect a certain lack of knowledge of the evidence-based indications for prophylaxis stated in the guidelines. 11,19,24 Because the guidelines' recommendations have been demonstrated to be widely applicable in daily practice 9,12,19,26,27 and previous studies in local settings have demonstrated the usefulness of specific training to improve management's adequacy, 4,16,28 educational efforts to increase physicians' adherence to the guidelines appear warranted and constitute a third area of management improvement found in our study.…”
Section: Discussionmentioning
confidence: 83%
“…25 In this way, the relevant increase in the prescription of anticoagulants to high-risk patients found in Spanish EDs during this century, from 28% in the GEFAUR-1 study to 69% in HERMES-AF, 9 is promising and supports the concept that adequate thromboprophylaxis is desirable and also feasible in ED patients with atrial fibrillation. 3,8,9,12,19,26 A main reason argued by the treating physicians for not prescribing anticoagulation was that they did not consider this treatment as indicated, despite that all patients included in the analysis were at high risk and without contraindications for anticoagulation. As in other studies, this may reflect a certain lack of knowledge of the evidence-based indications for prophylaxis stated in the guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…4,[6][7][8] Recent evidence suggests that aggressive protocols of ED cardioversion (pharmacologic or electrical) in patients with recent-onset paroxysmal atrial fibrillation or flutter are both safe and feasible. [9][10][11] Uptake of these protocols in clinical practice, as opposed to the traditional approach of exclusive rate control and stroke prevention, has been variable. 6 And although ED cardioversion for select patients with atrial fibrillation or flutter may be safe and effective, its ramifications on patient-oriented outcomes have not been well studied.…”
Section: Introduction Backgroundmentioning
confidence: 99%